β-Arrestin 2 is required for B1 receptor-dependent post-translational activation of inducible nitric oxide synthase - Kuhr, Frank K. (The Federation of American Societies for Experimental Biology, 2010)
A major source of “high-output” NO in inflammation is inducible nitric oxide synthase (iNOS). iNOS is primarily transcriptionally regulated and is thought to function as an uncontrolled generator of high NO. We found that iNOS in cytokine-stimulated human lung microvascular endothelial cells (HLMVECs) is highly regulated post-translationally via activation of the B1 kinin G protein-coupled receptor (B1R). We report here that B1R-mediated iNOS activation was significantly inhibited by knockdown of β-arrestin 2 with siRNA in cytokine-treated HLMVECs or HEK293 cells transfected with iNOS and B1R. In contrast, β-arrestin 1 siRNA had no effect. The prolonged phase of B1R-dependent ERK activation was also inhibited by β-arrestin 2 knockdown. Furthermore, robust ERK activation by the epidermal growth factor receptor (a β-arrestin 2 independent pathway) had no effect on iNOS-derived NO production. β-arrestin 2 and iNOS coimmunoprecipitated, and there was significant fluorescence resonance energy transfer between CFP-iNOS and β-arrestin 2-YFP (but not β-arrestin 1-YFP) that increased 3-fold after B1R stimulation. These data show that β-arrestin 2 mediates B1R-dependent high-output NO by scaffolding iNOS and ERK to allow post-translational activation of iNOS. This could play a critical role in mediating endothelial function in inflammation.—Kuhr, F. K., Zhang, Y., Brovkovych, V., Skidgel, R. A. β-Arrestin 2 is required for B1 receptor-dependent post-translational activation of inducible nitric oxide synthase.